Pengaruh Label Halal dan Religiusitas terhadap Keputusan Pembelian Produk Kosmetik di Kota Banda Aceh - Indina Tazkiya Lubis; Muhammad Yasir; Nevi Hasnita (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2024)
This study aims to analyze the influence of halal labeling and religiosity on purchasing decisions for beauty products, as well as to examine the moderating role of gender in the functional relationship between these two variables. The research sample consists of 100 cosmetic product users in Banda Aceh, selected through purposive sampling. Data collection was carried out using an online questionnaire, and the data were subsequently analyzed using multiple linear regression and moderated regression analysis. The study found that both halal labeling and religiosity have a positive and significant effect on purchasing decisions for cosmetic products. The greater the importance consumers place on halal labeling and the higher their level of religiosity, the more likely they are to purchase cosmetic products